(untitled) (Research, Society and Development, 2020)
The seed is considered the main agricultural input, being fundamental for the success of the production. For a seed to be considered of excellence, it must have physical, physiological, genetic and sanitary quality. These being the determining factors for her to be able to express her full potential. The attack of phytopathogenic agents affects the success of agricultural production, since it can limit the growth and development of crops. In addition to the fact that seeds are considered efficient sources of dissemination of pathogens, among the main ones are fungi, bacteria, viruses and some nematodes. Thus, the adoption of control methods is fundamental to prevent pathogens from being transmitted by seeds, such as chemical, physical, biological and alternative control, such as the use of extracts and vegetable oils. The adoption and efficiency of these pathogen control techniques found in the seeds, involves preventive treatment and their effectiveness in combating those of the organisms present internally and externally adhered to the seeds, enabling the maintenance of their quality.